Case Report: Microfragmented Adipose Tissue Drug Delivery in Canine Mesothelioma: A Case Report on Safety, Feasibility, and Clinical Findings - Zeira, Offer; Ghezzi, Erica; Pettinari, Letizia; Re, Valentina; Lupi, Davide M.; Benali, Silvia L.; Borgonovo, Simone; Alessandri, Giulio; Petrella, Francesco; Paroni, Rita; Dei Cas, Michele; Tremolada, Carlo; et al. (Frontiers in Veterinary Science, 2021)
Mesothelioma is a rare lethal tumor of dogs and humans involving cavities of the body. Dogs are considered a model for new drugs and therapeutic methods since they present spontaneous diseases similar to humans. Microfragmented adipose tissue (MFAT) uploaded by paclitaxel (PTX) is a drug delivery medium providing slow release of chemotherapic drugs. A dog affected by pleural, pericardial, and peritoneal mesothelioma was treated by 17 intracavitary ultrasound-guided injections of MFAT-PTX over 22 months. A long-lasting improvement of general conditions was observed, treatment was well-tolerated, and no toxicity or hypersensitivity was reported. Pharmacokinetic (PK) data indicated low drug localization in the circulatory system and a tendency to enter or remain in the extravascular compartments of the body. Indeed, low levels of free-circulating drugs for a short time produced low toxicity, whereas, a higher intracavitary PTX concentration can have major pharmacological efficacy. To our knowledge, this is the first time that mesothelioma has been treated using such a procedure, and this should be considered as a novel therapeutic approach. The low systemic absorption suggests the possible role of MFAT-PTX for loco-regional/intratumoral therapy also useful in other types of tumors, and further investigation is warranted.